2007
DOI: 10.1016/j.jss.2007.03.062
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preexisting Pathology in the Development of Neointimal Hyperplasia in Coronary Artery Bypass Grafts

Abstract: The degree of NH at baseline, a phenomenon exclusive to SVG and not found in arterial grafts, was significantly related to the development of lumen loss in the conduit over the first year after CABG. The study of SVG using serial CTA may provide unique insights into the natural history of SVG remodeling and to identify factors that influence the long-term function of this conduit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…3). The histologic findings in the present study are similar to other studies that have evaluated saphenous veins harvested at the time of coronary artery bypass grafting (CABG) surgery (2022). In their series of 46 saphenous vein segments and 27 internal mammary arteries, Friedl et al reported neointimal hyperplasia was present from 67% of veins vs. 29.6% of arteries (p<0.05) used in coronary artery bypass surgery (22).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…3). The histologic findings in the present study are similar to other studies that have evaluated saphenous veins harvested at the time of coronary artery bypass grafting (CABG) surgery (2022). In their series of 46 saphenous vein segments and 27 internal mammary arteries, Friedl et al reported neointimal hyperplasia was present from 67% of veins vs. 29.6% of arteries (p<0.05) used in coronary artery bypass surgery (22).…”
Section: Discussionsupporting
confidence: 86%
“…Preexisting vascular changes prior to development of CKD may also be quite relevant. Studies that have evaluated saphenous veins used for CABG have also shown that higher baseline intimal–media thickness ratio was significantly associated with development of lumen loss over the first year after CABG (21). Thus, studies from CAD and our study suggest that vascular injuries to the vein occur prior to development of advanced CKD, and in CAD these vascular injuries may possibly negatively affect clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Th e degradation of extracellular matrix by MMPs, which provides a structural framework essential for the functional properties of vessel wall, was found to be a prerequisite for smooth muscle cells migration, a critical step in neointima formation [27]. Moreover, baseline level of MMP-2 in the saphenous vein wall was shown to have a strong linear correlation with the degree of luminal narrowing at 1 year aft er coronary artery bypass graft [32]. Perek et al (2016) stated that saphenous vein segments may be more appropriate graft s in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of ECM by MMPs, which provides a structural framework essential for the functional properties of vessel wall, was found to be a prerequisite for SMCs migration, a critical step in neointima formation [4]. Moreover, baseline level of MMP-2 in the SV wall was shown to have a strong linear correlation with the degree of luminal narrowing at 1 year after CABG [17]. Our finding of an association between MMP-2 expression and degree of differentiation of the venous SMCs in the tunica media supports the observations of Xiao et al who showed a negative association between production of MMP-2 and degree of differentiation of the medial SMCs in the SV segments derived from varicose veins [15].…”
Section: Discussionmentioning
confidence: 99%